Vascular Endothelial Growth Factor as a Potential Biomarker of Neuroinflammation and Frontal Cognitive Impairment in Patients with Alcohol Use Disorder - Requena-Ocaña, Nerea; Flores-López, María; Papaseit, Esther; García-Marchena, Nuria; Ruiz-Ruiz, Juan Jesús; Ortega-Pinazo, Jesús; Serrano, Antonia; Pavón-Morón, Francisco Javier; Farré, Magí; Suárez-Pérez, Juan; Rodriguez-de-Fonseca, Fernando; Araos Gómez, Pedro Fernando (IOAP-MPDI, 2022)
(1) Background: Alcohol Use Disorder (AUD) is associated with functional disruption of several brain structures that may trigger cognitive dysfunction. One of the mechanisms of alcohol-associated cognitive impairment has been proposed to arise from its direct impact on the immune system, which culminates in the release of cytokines and chemokines which can eventually reach the brain. Alcohol can also disrupt the blood–brain barrier, facilitating the penetration of pro-inflammatory molecules throughout vascular endothelial growth factor A (VEGFA). Thus, alcohol-induced alterations in chemokines and VEGFA might contribute to the neuroinflammation and cognitive impairment associated with AUD. (2) Methods: The present cross-sectional study investigates whether patients with AUD (n = 86) present cognitive disability associated to alterations in plasma concentration of SDF-1, fractalkine, eotaxin, MCP-1, MIP-1α and VEGFA when compared to control subjects (n = 51). (3) Results: The analysis indicated that SDF-1 and MCP-1 concentrations were higher in AUD patients than in controls. Concentrations of VEGFA were higher in AUD patients with severe frontal deficits, and the score of frontal lobe functions was negatively correlated with VEGFA and fractalkine. Acute alcohol effects on VEGFA plasma levels in healthy volunteers demonstrated the induction of VEGFA release by heavy alcohol drinking. VEGFA was positively correlated with pro-inflammatory chemokines in AUD patients with frontal cognitive impairment. (4) Conclusions: we propose VEGFA/chemokine monitoring as biomarkers of potential cognitive impairment in AUD patients.
Keywords: Alcohol; Alcohol use disorders; Addiction; VEGFA; Blood–brain barrier; Chemokines; Fractalkine; Neuroinflammation; Cognitive dysfunction; Neurodegeneration; Dementia